Sleep quality and associated factors among university students in Africa: a systematic review and meta-analysis study - Nakie, Girum; Takelle, Girmaw Medfu; Rtbey, Gidey; Andualem, Fantahun; Tinsae, Techilo; Kassa, Mulat Awoke; Tadesse, Gebresilassie; Fentahun, Setegn; Wassie, Yilkal Abebaw; Segon, Tesfaye; Kibralew, Getasew; Melkam, Mamaru (Frontiers in Psychiatry, 2024)
Poor sleep quality significantly impacts academic performance in university students. However, inconsistent and inconclusive results were found in a study on sleep among university students in several African nations. Therefore, this study aimed to estimate the pooled prevalence and associated factors of poor sleep quality among university students in Africa.The databases PubMed, Scopus, Cochrane Library, Science Direct, African Journal Online, and Google Scholar were searched to identify articles. A total of 35 primary articles from 11 African countries were assessed and included in this systematic review and meta-analysis. Data were extracted by using a Microsoft Excel spreadsheet and exported to STATA version 14 for analysis. The I 2 test was used to assess the statistical heterogeneity. A random effect meta-analysis model was employed with 95% confidence intervals. Funnel plots analysis and Egger regression tests were used to check the presence of publication bias. A subgroup analysis and a sensitivity analysis were done.Results: A total of 16,275 study participants from 35 studies were included in this metaanalysis and systematic review. The overall pooled prevalence of poor sleep quality among university students in Africa was 63.31% (95% CI: 56.91-65.71) I 2 = 97.2. The subgroup analysis shows that the combined prevalence of poor sleep quality in East, North, West, and South Africa